Anatomical and Physiological Characteristics of Neonatal and Infant Skin: Effects on Immunity and Dermatitis Prevalence - Nurhidayati; Mario, Andina Nabilah; Girsang, Andrew Deardo Purba; Srigede, Baiq Kayla; Hadiyati, Fathmi; Pramudya , I Nengah Andra Putra; Saraswati, Ni Wayan Citra Ayu; Helmiana, Putri Fatimah; Pramudia, Prananda Rizki; Fildzani, Qashrina Vania; Tarigan, Rizky Agung Fatahillah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The skin has an important role in protecting the human body. However, in infants, the skin has a structure and function that are not fully mature yet, making infants vulnerable to various skin disorders. This article aims to review the structure, function, and development of infant skin, as well as the common diseases that occur in infant skin, including the causes, pathophysiology, and management. A literature review was conducted using scientific articles related to these topics. The review results show that infant skin has a different structure compared to adult skin, and the maturation of its structure and function occurs gradually. Infant skin is protected by the microbiota and the primary immune system. Common skin diseases in infants, such as dermatitis, are caused by an interaction between genetic and environmental factors, and involve the activation of skin cells, the release of mediators, and an immune response. A good understanding of the structure, function, and skin diseases of infants is very important for making the right diagnosis and management, so that the quality of life of infants can be maintained.